Positive culture's role in building Profil Pelajar Pancasila character - Helena Anggraeni Putri; Wuri Astiwi (Curricula: Journal of Curriculum Development, 2025)
This study aims to explain the implementation of positive culture in shaping the character of Profil Pelajar Pancasila among students at Totogan Elementary School. The research employed a descriptive qualitative method, with data collection techniques including observation, interviews, and documentation. The findings reveal various forms of positive culture implementation in the school, such as the establishment of classroom agreements that create a safe and conducive learning environment, the application of the restitution triangle to help students set goals, develop positive discipline, and recover after making mistakes, as well as daily routines outlined in the school's SOP to strengthen character in line with the Profil Pelajar Pancasila. Additionally, various extracurricular activities, both mandatory and optional, provide opportunities for students to develop their potential, talents, and interests in fields such as science, general knowledge, religion, and sports. Based on these findings, it can be concluded that implementing positive culture plays a significant role in shaping the Profil Pelajar Pancasila. This demonstrates that the positive culture applied at Totogan Elementary School has successfully been the foundation for developing students' characters in alignment with the Profil Pelajar Pancasila within the current Kurikulum Merdeka.   Abstrak Penelitian ini bertujuan untuk menjelaskan penerapan budaya positif dalam membentuk karakter Profil Pelajar Pancasila di kalangan siswa Sekolah Dasar Totogan. Metode yang digunakan adalah penelitian kualitatif deskriptif, dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa terdapat berbagai bentuk implementasi budaya positif di sekolah, seperti pembentukan keyakinan kelas yang menciptakan lingkungan belajar yang aman dan kondusif, penerapan segitiga restitusi yang membantu siswa memiliki tujuan, disiplin positif, dan memulihkan diri setelah melakukan kesalahan, serta pembiasaan harian yang tercantum dalam SOP sekolah untuk memperkuat karakter sesuai dengan Profil Pelajar Pancasila. Selain itu, berbagai kegiatan ekstrakurikuler, baik wajib maupun pilihan, memberikan wadah bagi siswa untuk mengembangkan potensi, bakat, dan minat mereka dalam bidang sains, pengetahuan umum, agama, dan olahraga. Berdasarkan temuan ini, dapat disimpulkan bahwa penerapan budaya positif berperan penting dalam mewujudkan karakter Profil Pelajar Pancasila. Hal ini menunjukkan bahwa budaya positif yang diterapkan di Sekolah Dasar Totogan telah berhasil menjadi landasan terbentuknya karakter siswa yang sesuai dengan profil pelajar Pancasila dalam Kurikulum Merdeka yang berlaku. Kata Kunci: budaya positif; Profil Pelajar Pancasila; sekolah dasar